Analisis prosedur inventarisasi Barang Milik Daerah (BMD) berdasarkan Permendagri Nomor 47 Tahun 2021 (Studi kasus Dinas Sosial Daerah Provinsi Sulawesi Utara) - Allo, Rohayani Linggi’; Walandouw, Stanley Kho; Datu, Christian (Riset Akuntansi dan Manajemen Pragmatis, 2024)
Inventory of Regional Property (BMD) is an important process in managing regional assets. Inventory activities to collect data, record, and report the results of data collection of Regional Property. This study aims to determine the implementation of the Regional Property Inventory Procedure based on Permendagri Number 47 of 2021 at the Regional Social Service of North Sulawesi Province. This type of research is qualitative research with a case study approach. Data collection methods through interviews, observation, and documentation. The data analysis process is carried out by collecting data which is then grouped and then analyzed and described. The results of this study indicate that the Regional Property inventory procedure carried out at the Regional Social Service of North Sulawesi Province is in accordance with Permendagri Number 47 of 2021 concerning Procedures for Implementing, Bookkeeping, Inventory, and Reporting Regional Property. However, there are still obstacles where the implementation of E-BMD is still not optimal so that it does not accommodate the entire implementation of the inventory of Regional Property at the Regional Social Service of North Sulawesi Province.